La adquisición de lenguas en contexto online: entre la innovación y la optimización - Mora, António Chenoll (2021)
It is impossible not to learn. Every average brain is capable of acquiring new declarative knowledge in any context. What matters in the formal learning process is the optimization in the triangle created between the effort dedicated in this process, the quality of learning and the unchangeable durability of the developed competences. In this sense, innovation is a concept empty of meaning from the point of view of learning. We do not just need methods, contexts or new hardware; we need improved methods, contexts and hardware that are adapted to our current needs. Therefore, learning in the digital context minimizes many of the impediments that keep us from obtaining a more adequate optimization level, but like learning in manuals, we must select what gets better results in the optimization context of active learners. This paper will critically analyze the concept of innovation and its connection with optimization in the process of acquisition of non-native languages in an on-line context.